1997
DOI: 10.3109/00016349709024602
|View full text |Cite
|
Sign up to set email alerts
|

Underreporting and misclassification of maternal mortality in Taiwan

Abstract: This study shows the limitations of official vital registration and concludes that dependence on death certificates alone to identify maternal deaths is incomplete and incorrect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 22 publications
5
22
0
3
Order By: Relevance
“…Applying the method described and used by Kao et al [10], the authors classified death as bpreventableQ when feasible actions, if taken, could have prevented it, and as btreatableQ when its cause was considered amenable to treatment within the scope of resources and services available in the West Bank. Direct preventable causes of maternal death included postpartum hemorrhage, pre-eclampsia/eclampsia, postoperative bleeding complications, postcesarean sepsis, and uterine rupture; indirect preventable causes included thromboembolism, cardiac failure, and anemia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Applying the method described and used by Kao et al [10], the authors classified death as bpreventableQ when feasible actions, if taken, could have prevented it, and as btreatableQ when its cause was considered amenable to treatment within the scope of resources and services available in the West Bank. Direct preventable causes of maternal death included postpartum hemorrhage, pre-eclampsia/eclampsia, postoperative bleeding complications, postcesarean sepsis, and uterine rupture; indirect preventable causes included thromboembolism, cardiac failure, and anemia.…”
Section: Methodsmentioning
confidence: 99%
“…For example, in Taiwan, under-reporting has been shown to occur 58% of the time and correct classification merely 53% of the time [10]; and in Mozambique, a community-based study on the quality of registration of maternal deaths reported that up to 86% of maternal deaths were unregistered [11].…”
Section: Introductionmentioning
confidence: 98%
“…If so, the rapid increase in frequency of cesarean deliveries in Tunisia should incite obstetricians to resort to this procedure only in well-documented and justified contexts. Underreporting of maternal deaths remains a recurrent problem (even in high-income countries with well-established national maternal death registers), leading to underestimation of the true MMR [16,17]. In Tunisia, it can reasonably be supposed that underreporting of maternal deaths does occur.…”
Section: Discussionmentioning
confidence: 96%
“…The RAMOS has been used in assessments of maternal mortality in hospitals in several low-resource countries, including Surinam, Tanzania, Gambia, Mozambique, and Taiwan [1,2,[5][6][7][8]. In all of these studies, the use of the RAMOS increased the identification of maternal deaths compared with hospital records and official government estimates.…”
Section: Introductionmentioning
confidence: 99%
“…Investigative studies routinely uncover significant underreporting of maternal mortality in low-resource countries; in rural areas, and at the community level, maternal mortality is notoriously difficult to identify [1][2][3]. National birth and death certification processes are variably implemented, and data collection frequently does not extend into the rural communities where many maternal deaths occur.…”
Section: Introductionmentioning
confidence: 99%